Lesiones esplénicas secundarias a traumatismos abdominales - Fiallos Zamora, Joselyn Stephanie (2023)
ABSTRACT: The present literature review identified that splenic injuries secondary to abdominal trauma could have various clinical features, including abdominal pain, tenderness in the splenic area, signs of internal bleeding, hypotension, and signs of shock. Splenic lesions are diagnosed using imaging techniques, such as computed tomography (CT) or abdominal ultrasound. Treatment of splenic injuries can be conservative or surgical, depending on the injury's severity and the patient's hemodynamic stability. Complications of splenic injuries may include hemorrhage, splenic rupture, infection, abscess formation, hypersplenism, and diaphragmatic eventration. Epidemiological characteristics reveal that young men have a higher incidence of splenic injuries secondary to abdominal trauma, and factors such as automobile accidents falls from heights, and sports injuries are common. Understanding these characteristics helps to identify high-risk groups and guide preventive strategies. The prognosis of splenic injuries secondary to abdominal trauma may vary depending on the severity of the injury, the promptness of diagnosis and treatment, and the individual patient's response. It is essential that the treatment of splenic injuries is carried out in an appropriate hospital environment and under the supervision of a medical team experienced in managing abdominal and splenic injuries. Properly managing splenic injuries secondary to abdominal trauma is essential to prevent serious complications and improve the patient's prognosis. An individualized evaluation, accurate diagnosis, and adequate treatment are crucial to achieving favorable results in these cases. In general, it is recommended to improve clinical training, increase awareness of splenic injuries secondary to abdominal trauma, implement prevention strategies aimed at high-risk groups, and adopt a multidisciplinary approach to the management and early detection of complications. These actions will improve the recognition, treatment, and outcomes of patients with these lesions. Keywords: abdominal injuries, splenic trauma, spleen, diagnosis.